GE_GERICHTE C/14140/2014 vom 26. Oktober 2015 - GE Cour de justice (2015)
CAS CLAIR; EXPULSION DE LOCATAIRE; CONTESTATION DU CONGÉ; NOUVEAU MOYEN DE FAIT; PAIEMENT DE L'ARRIÉRÉ | CPC.257; CPC.317; CO.257d; CO.257c; CO.18; CO.271.1; CCR.1.1